INCREASING STUDENT LEARNING INTEREST USING THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ASSISTED BY PUZZLE MEDIA IN SCIENCE LEARNING FOR GRADE IV OF KAYUAPU ELEMENTARY SCHOOL - Muhammad Yusril Falaah; Sekar Dwi Ardianti; Yuni Ratnasari (PIONIR: JURNAL PENDIDIKAN, 2025)
This research aims to increase students' interest in learning science and science by implementing the Problem Based Learning (PBL) learning model assisted by puzzle media for class IV at Kayuapu Elementary School. This research uses Classroom Action Research (PTK). The number of respondents in this research was 15 grade IV students at Kayuapu Elementary School. The instrument used to collect data was a student interest questionnaire. The data obtained was analyzed using descriptive analysis which was used to determine students' interest in learning. The results of the research show that learning using the Problem Based Learning (PBL) learning model assisted by puzzle media can increase the learning interest of fourth grade students at Kayuapu Elementary School. This can be seen from the activities before the action, the average completion of students' learning interest results reached 60.4% in the low category. In cycle I, the average completion of learning interest results reached 72.4% in the "good" category. And in the second cycle, students' interest in learning increased to 85.6 in the "very good" category. Thus, it can be concluded that the application of the Problem Based Learning (PBL) learning model assisted by puzzle media can increase the learning interest of fourth grade students at Kayuapu Elementary School. Keywords: Interest in Learning, Problem Based Learning (PBL) Learning Model, Puzzles.